Physiological responses of Bos taurus and Bos indicus cows submitted to hormonal treatments for estrous cycle synchronization - Silva, Lucas Oliveira e (2020)
Three studies were performed to evaluate the physiological responses of Bos taurus and Bos indicus females submitted to hormonal strategies for estrous cycle synchronization. In the first study, the circulating progesterone (P4) profile provided by 10 intravaginal P4 implants was evaluated, as well as the effect of circulating P4 concentrations on dominant follicle (DF) development. Then, non-lactating Holstein and Nelore cows without corpus luteum (CL) received one of the P4 implants associated to 2 mg estradiol benzoate (EB), to synchronize follicular emergence. The P4 implants were kept for 14 d. Daily blood samples were taken and ultrasound evaluation was performed. Overall, all implants were able to increase circulating P4 concentrations and induce emergence of a new follicular wave, associated to EB. Moreover, greater P4 concentrations were provided by implants with greater surface area or greater initial P4 load. In addition, higher P4 concentrations (mainly during the first 3 d) were associated with lower DF size at 7 d after implant insertion, for both breeds. In the second study, non-lactating Holstein cows were presynchronized and, on day 7 of the estrous cycle, they were assigned to have or not a functional CL. On this day, all cows received 100 µg gonadorelin (GnRH), and simultaneously, they were designated to receive or not a P4 implant (2 g). Ultrasound evaluations were performed to check the ovulatory response to GnRH and the subsequent CL development, and blood samples were taken to evaluate circulating P4 and LH concentrations. Cows with CL presented higher circulating P4 at the time of GnRH and, consequently, lower LH release and ovulation (with CL = 58.1%; without CL = 95.5%). However, P4 implant insertion did not affect the LH release or ovulation. Moreover, higher P4 concentrations at the time of GnRH were associated with lower ovulatory response, and the opposite effect was observed in relation to the LH peak amplitude induced by GnRH. Additionaly, the development/maintance of subsequent CL was negatively affected by CL presence and P4 implant insertion at the time of GnRH treatment. In the third study, cycling Nelore heifers and non-lactating Nelore cows were presynchronized and, on day 7 of the estrous cycle, they were designated to receive gonadorelin (100 or 200 µg) or buserelin (10 or 20 µg). At the time of treatments, circulating P4 concentrations was similar among heifers and cows (~4 ng/mL). In heifers, regardless of dose, buserelin treatments induced greater LH peak and ovulation than gonadorelin (88.9 vs. 16.7%). In addition, the double dose increased LH release only in the buserelin treatment. Otherwise, in cows, although the double dose had increased LH release in both GnRH analogues, only the double dose of buserelin produced high ovulatory response (90.9%), whereas in the other treatments ovulation did not differ (35.7%). In both animal categories, higher LH peak was associated to greater ovulatory response, but in heifers, ovulation was triggered by LH peaks with lower amplitude than cows.